2017
DOI: 10.1063/1.5003134
|View full text |Cite
|
Sign up to set email alerts
|

Terahertz electromagnetic radiation based on the interaction between a self-modulated electron beam and plasma wakefield

Abstract: This particle-in-cell simulation study finds that the system of a long relativistic electron beam passing through an overdense plasma can produce high harmonic terahertz electromagnetic radiation. In this process, the electron beam is self-modulated to create a periodic electromagnetic structure which will resonate with the plasma wakefield and excite the electromagnetic instability in the nonlinear stage of the self-modulation. The study also finds that when the radiation is achieved, the self-modulated elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Recently, a new kind of high-power THz source, called electron beam-plasma system (EBPS) has attracted wide attention [16][17][18][19][20][21][22][23][24][25][26][27][28][29]. This THz source does not have a damage threshold as the plasma is in a highly ionized state.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a new kind of high-power THz source, called electron beam-plasma system (EBPS) has attracted wide attention [16][17][18][19][20][21][22][23][24][25][26][27][28][29]. This THz source does not have a damage threshold as the plasma is in a highly ionized state.…”
Section: Introductionmentioning
confidence: 99%
“…Previous experiments have successfully observed powerful THz radiation from EBPS in a large magnetic confinement plasma device [16][17][18]. Meanwhile, various related THz radiation mechanisms have also been investigated [19][20][21][22][23][24][25][26][27][28][29]. It can be found that all the previous studies adopt linear schemes considering a single beam or two counterstreaming beams passing through a plasma column.…”
Section: Introductionmentioning
confidence: 99%
“…Generation of electromagnetic (EM) waves near harmonics of the plasma frequency 𝜔 𝑝 during collective beam-plasma interaction is a well known phenomena that is frequently observed in both space and laboratory plasmas. Presently, processes of linear and nonlinear conversion of beam-driven electrostatic plasma waves into EM radiation are actively studied in relation to solar radio bursts [1][2][3][4] and the problem of high-power terahertz generation [5][6][7][8][9]. If the beam-to-radiation power conversion in the latter problem is increased up to a few percent, radiation sources based on multi-GW electron beams will be able to achieve the record gigawatt level of terahertz power.…”
Section: Introductionmentioning
confidence: 99%
“…The emission of THz radiation by the photoelectron current induced by the ionization of a gas due to non-linear mixing of the fundamental and second harmonic of ultra-short laser pulses was studied analytically by Kim et al [15] Recently, the excitation of electromagnetic waves by the interaction of a self-modulated electron beam and an over-dense plasma was studied by Yang et al [16] by using particle-in-a-cell (PIC) simulation. Because of the resonance between the plasma wakefield and the electron beam, plasma oscillations are amplified to generate THz radiation.…”
Section: Introductionmentioning
confidence: 99%